PREGNANCY RATES IN COWS INSEMINATED WITH CONVENTIONAL NON-SORTED AND GENDER SORTED SEMEN UNDER FIELD CONDITION - TUMBARE, P J; AMLE, M B; KHILLARE, K P; RANGNEKAR, M N; MALIK, A B; DHAYGUDE, V S (The Indian Journal of Animal Reproduction, 2023)
The study was designed to compare the efficacy of conventional and gender sorted semen in cows. Overallpregnancy rate was 57.14 %, when cows were inseminated with conventional non-sorted semen. Cows inseminatedwith gender sorted semen resulted in overall pregnancy rate of 50.00 %. The results revealed no significant difference(p>0.05) in conception rates between the groups of cows. The overall conception rate in this study including cowsfrom both the groups was found to be 53.57 %.
Keywords: Cows; AI; Conventional non-sorted semen; Gender Sorted Semen; Pregnancy Rate